Information System Development of Master’s and Doctoral Study Task Recommendation Using Fuzzy AHP - Nurul Ni'mah; Yunarso Anang (Politeknik Statistika STIS, 2021)
In improving quality of employees through education, Statistics Indonesia is assisted by Education and Training Centre, one of them through the Study Task program at Master's and Doctoral degrees. Due to the decrease of registrant as candidate participants of this program and to facilitate employees proposed, information system for providing recommendations Study Task program is needed. This research aims to provide recommendations to employees who are highly, moderately or not recommended being able to continue education with Study Task program using an information system. Decision-making in system is Fuzzy Analytic Hierarchy Process (Fuzzy AHP) method with assessment criteria, sub-criteria and their weights can be changed by certain actors. The system was built using the Framework for the Application of Systems Thinking (FAST) method. The system was evaluated by Black Box Testing with the results of all functions running well and System Usability Scale with results of 80.71 which means the system can be received by users. Finally, this system is expected to assist the selection of employees and provide opportunities for employees who are able to continue their education with Study Task program efficiently and reduce the subjectivity of the assessment.